Authenticity Model of (Mass-Oriented) Computer-Mediated Communication: Conceptual Explorations and Testable Propositions. Issue 1 (20th January 2020) - Lee, Eun-Ju
Abstract: While several major theories and models have emerged and guided research on computer-mediated communication (CMC) in the interpersonal context, equivalent theoretical development seems to be lacking in the study of mass-oriented CMC, despite a large volume of amassed research. This article aims to propose an integrative conceptual framework for the study of mass-oriented, including mass-personal CMC, with (perceived) authenticity as its core unifying construct. A range of theoretical constructs independently developed in various subdisciplines and pertinent research findings are reviewed in light of the authenticity of source, message, and interaction. Several testable propositions are derived concerning antecedents to and consequences of authenticity judgments, with a view to stimulating programmatic empirical investigations on the role of authenticity in CMC.